Thermodynamic Performance Analysis of Food Refrigeration Machine on MT. YN Busan Ship in Supporting Food Quality During Sailing - Arham, Muhammad; Zainuddin, Muhammad; Mubarak, Husni; Hamka, Akhsan (International Journal of Management and Education in Human Development, 2025)
This study examines the performance of the food refrigeration system on the MT. YN Busan tanker during international voyages across Korean, Yellow Sea, Chinese, and Japanese waters. The main objectives are to calculate the compressor work capacity ( ), the heat absorption capacity of the evaporator ( ), the heat rejection capacity of the condenser ( ), and the Coefficient of Performance (COP). In addition, the study evaluates the quality of food stored in the refrigerated compartments. Data were collected through measurements of compressor pressure and temperature, expansion valve temperature, and refrigerated room temperature. The analysis was conducted using the R-404A refrigerant ph diagram and evaluated based on the Minimum Energy Performance Standards (MEPS) for air conditioners and refrigeration systems. The results show that the highest was 28.9 kJ/kg in Korean waters at 12:00, while the lowest was 27.7 kJ/kg in Chinese waters at 20:00. The highest was recorded at 236 kJ/kg in the meat storage room in the Yellow Sea, while the lowest was 231.5 kJ/kg in Korea. The highest was 263.6 kJ/kg in both the Yellow Sea and China, with the lowest value of 260.3 kJ/kg in Korea. The highest COP was observed in the meat storage room, reaching 8,551 in the Yellow Sea, while the lowest was 8,038 in Korea. All COP values were ≥ 6, thus classified as excellent performance. However, food quality testing revealed that only 5 out of 16 temperature measurement points in the meat storage room and 7 out of 16 points in the vegetable storage room met the refrigeration system specifications. In conclusion , the refrigeration system demonstrated excellent performance, but the temperature distribution in the storage compartments was not yet uniform. This uneven distribution could affect food quality during the voyage and requires further optimization.